2010
DOI: 10.1109/jsen.2010.2049199
|View full text |Cite
|
Sign up to set email alerts
|

A Fiber Bragg Grating Sensor System for Train Axle Counting

Abstract: Railway signaling facilitates two main functions, namely, train detection and train control, in order to maintain safe separations among the trains. Track circuits are the most commonly used train detection means with the simple open/close circuit principles; and subsequent adoption of axle counters further allows the detection of trains under adverse track conditions. However, with electrification and power electronics traction drive systems, aggravated by the electromagnetic interference in the vicinity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…Wei et al 43 used FBG sensors to count the axles, which pass the sensors. The main problem here is the processing of noisy signals.…”
Section: W1 ¼ P1 ð6þmentioning
confidence: 99%
See 1 more Smart Citation
“…Wei et al 43 used FBG sensors to count the axles, which pass the sensors. The main problem here is the processing of noisy signals.…”
Section: W1 ¼ P1 ð6þmentioning
confidence: 99%
“…For example, in Wei et al 43 and Filograno et al, 44 different positions for mounting the sensors were assessed. Wei et al 43 implemented an ANSYS analysis and laboratory test. Their results showed that the maximum deflection would be on the head and foot of the rail in case of longitudinal sensor.…”
Section: Measurement Conditionsmentioning
confidence: 99%
“…The interrogation equipment, referred as si425 optical sensing interrogator, designed by Micro Optics, INC. and used in this study, is based upon the wavelength-division multiplexing technique. In simple terms, an interrogation system is a scanning ring laser [3]. A light outputs from a wavelength-tunable laser, and a certain wavelength of light is reflected by the FBG sensors, and the reflected component is detected by photo detectors.…”
Section: B the Interrogation Systemmentioning
confidence: 99%
“…They could detect the train parameters: train speed and acceleration, the distance between the wheels and the total number of wheels. Moreover, by studying the electromagnetic interference (EMI) on the delicate changes of the FBG's measurements, Wei et al (2010); Wei et al (2012) proposed an approach of axle counting with two methods presented: X-Crossing and D(erivative)-Crossing. In fact, a peak in the signal is determined by a rising edge, followed by a falling edge.…”
Section: Introductionmentioning
confidence: 99%